Endocrine Disruption and Reproductive Pathology. (December 2019) - Belcher, Scott M.; Cline, J. Mark; Conley, Justin; Groeters, Sibylle; Jefferson, Wendy N.; Law, Mac; Mackey, Emily; Suen, Alisa A.; Williams, Carmen J.; Dixon, Darlene; Wolf, Jeffrey C.
During the past 20 years, investigations involving endocrine active substances (EAS) and reproductive toxicity have dominated the landscape of ecotoxicological research. This has occurred in concert with heightened awareness in the scientific community, general public, and governmental entities of the potential consequences of chemical perturbation in humans and wildlife. The exponential growth of experimentation in this field is fueled by our expanding knowledge into the complex nature of endocrine systems and the intricacy of their interactions with xenobiotic agents. Complicating factors include the ever-increasing number of novel receptors and alternate mechanistic pathways that have come to light, effects of chemical mixtures in the environment versus those of single EAS laboratory exposures, the challenge of differentiating endocrine disruption from direct cytotoxicity, and the potential for transgenerational effects. Although initially concerned with EAS effects chiefly in the thyroid glands and reproductive organs, it is now recognized that anthropomorphic substances may also adversely affect the nervous and immune systems via hormonal mechanisms and play substantial roles in metabolic diseases, such as type 2 diabetes and obesity.